Method for identifying properties of copper-containing solid waste
Through two mosaic sample preparation and scanning electron microscopy, combined with X-ray energy spectrometer, mineral analysis software is used to match mineral phases, and the problem of difficult to identify the properties of copper-containing solid waste in the existing technology is solved, achieving rapid and accurate identification. , reduces cost and time, and improves the comprehensiveness and accuracy of identification.
Patent Information
- Application Number
- CN202411340398.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
The existing technology is difficult to accurately identify the properties of solid waste containing copper. Traditional methods rely on appearance characteristics and experience, and lack relevant identification procedures and standard data, resulting in identification difficulties and errors. Conventional laboratory methods have many consumables and high labor costs, and the analysis time is long. , unable to meet the requirements of fast and accurate.
The copper-containing powder to be identified is mixed with conductive epoxy resin and curing agent, and then cured and inlaid, combined with scanning electron microscope and X-ray energy spectrometer analysis, and mineral analysis software is used to match the mineral phase. Extract the fingerprint characteristics of typical metallurgical copper-containing solid waste to quickly and accurately identify the properties of copper-containing solid waste.
Improve the comprehensiveness and accuracy of identification, reduce the cost of consumables and labor, shorten the analysis time, achieve rapid and accurate identification of copper-containing solid waste, overcome the result error caused by sample inhomogeneity, and can be reused Mosaic samples.
Smart Images

Figure CN119269561A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid waste identification, and in particular relates to a method for identifying the properties of copper-containing solid waste. Background Art
[0002] At present, the current national standard for the identification of solid waste properties is GB 34330-2017 "General Standards for the Identification of Solid Wastes". This standard defines solid wastes, but does not specify specific identification methods. At present, the commonly used identification method for the properties of imported non-ferrous metal solid wastes is based on appearance characteristics combined with the experience of supervisors. However, since most solid wastes containing non-ferrous metals are in powder, block, or mud form, they are difficult to distinguish from metal ores and are easily falsely reported as metal ores or imported mixed with metal ores, which brings great difficulties to the identification of the properties of non-ferrous metal solid wastes using traditional methods. The core and key point of solid waste identification is to accurately grasp the source of the material to be identified. Only by clarifying the source of generation can the target product in the process of producing the material to be identified be determined, and then it is known whether the material is a product, a by-product, or a substance produced in the pollution control facility or environmental governance process, as well as whether it is intentionally produced, whether there is quality control and other information, and then its solid waste properties are obtained. Since the identification of the properties of solid wastes containing non-ferrous metals involves multiple disciplines such as customs law, mineralogy, and solid waste identification, the identification is difficult. Moreover, there are currently no relevant identification procedures and standard data maps for this type of solid waste identification, which poses a great challenge to all related identification work. Therefore, it is urgent to develop efficient non-ferrous mining and metallurgical product solid waste attribute identification technology.
[0003] At present, the identification of metallurgical solid waste is mostly concentrated in the laboratory, usually including chemical analysis, polarizing microscopy, X-ray fluorescence spectroscopy, X-ray diffraction spectroscopy, inductively coupled plasma emission spectroscopy, atomic absorption spectroscopy, etc., by analyzing the composition, toxic and harmful substances, phase structure, polarizing microscopic morphology and other information, inferring the properties of solid waste. At the same time, the application of scanning electron microscopy to the identification of metallurgical solid waste is limited to observing the surface morphology characteristics of the sample, and is not used as one of the main identification methods. Most conventional laboratory solid waste property identification methods are limited to obtaining a single component content, morphology or phase results, and cannot directly determine whether it is solid waste. In addition, the required reagents consume a lot, the manpower and equipment costs are high, and the analysis time is long, which does not match the current large-scale customs clearance and trade facilitation The required fast and accurate requirements do not match. Summary of the invention
[0004] In view of the problems involved in the above-mentioned prior art, the present invention will provide a method for identifying the properties of copper-containing solid waste.
[0005] To achieve the above purpose, the following technical solutions are specifically included:
[0006] A method for identifying the properties of copper-containing solid waste comprises the following steps:
[0007] (1) drying and shaking the copper-containing solid to be identified to obtain a copper-containing powder;
[0008] (2) mixing the copper-containing powder, the conductive epoxy resin and the curing agent uniformly to obtain a mixture; transferring the mixture into two molds respectively, and curing to obtain two block samples;
[0009] (3) placing the two block samples in a mounting device in such a manner that the cross section of one block sample and the longitudinal section of the other block sample are in the same plane, adding a conductive mounting material, and mounting to obtain a mounted sample;
[0010] (4) polishing, cleaning and drying the mounted sample in sequence to obtain a sample to be tested;
[0011] (5) using a scanning electron microscope to test the sample to be tested, collecting the particle morphology characteristics, element types and their contents, and element surface distribution information on the sample in a backscattered electron mode, and using the mineral standard library in the mineral analysis software for matching analysis to determine the mineral phases and their contents in the sample, and obtain the particle size information, element information, and mineral information of the sample;
[0012] (6) comparing the particle size information, element information and mineral information of the sample with the fingerprint information of the copper-containing solid waste to determine whether the copper-containing solid to be identified is copper-containing solid waste;
[0013] The fingerprint information of the copper-containing solid waste includes at least one of particle size fingerprint information, element fingerprint information and mineral fingerprint information;
[0014] In the particle size fingerprint information, the average particle size of the copper-containing solid waste is ≥18 μm;
[0015] In the element fingerprint information, the copper-containing solid waste includes the following element components in mass percentage: S≤11%, Fe≤17%, Cu 5-32%, Ti≤1.5%, Zn≤1.5%, O 5-45%, Si≤30%, Ca≤10.5%, Al≤5.5%, K≤5.5%, Mg≤5.5%;
[0016] In the mineral fingerprint information, the copper-containing solid waste includes the following mineral phases in mass percentage: blue chalcocite 0.5-6%, Cu8S5 0.5-11%, chalcopyrite ≤16%, pyrite ≤10.5%, chalcopyrite ≤5.5%, and the remainder is other phases.
[0017] The present invention conducts scanning electron microscope analysis on suspected metallurgical copper-containing solid waste, and extracts typical metallurgical copper-containing solid waste fingerprint features for identification based on the surface microscopic morphology under the scanning electron microscope, the element composition content and element distribution information detected by the energy spectrometer, and the physical matching information analyzed by the mineral analysis software. The properties of the suspected metallurgical copper-containing solid waste can be quickly and accurately identified.
[0018] Scanning electron microscope (SEM) and X-ray energy spectrometer (EDS) can respectively analyze the microscopic morphology and composition of suspected metallurgical copper-containing solid waste, and obtain the morphology, particle size and composition information of suspected metallurgical copper-containing solid waste. The morphology and composition information are then used as the mineral phase and structure information of mineral analysis, matched with the mineral standard library, to determine the mineral phase and content information of the suspected metallurgical copper-containing solid waste.
[0019] The SEM, EDS and mineral analysis software are configured as one. The mineral analysis method integrates SEM technology, and multiple SEM images can be spliced into a representative overall area, overcoming the shortcomings of SEM that can only perform microscopic morphology and composition analysis, and can deconvolute the X-ray spectrum of the mixed phase, thereby realizing the analysis of the mixed phase. This technology can fill the gap between microscopic analysis based on microscopic technology and macroscopic composition analysis, thereby more accurately judging the solid waste properties of the sample.
[0020] In addition, since metallurgical copper-containing solid waste usually involves tailings, slag, mineral products and other categories, which are poor in lithium or complex in type, and in terms of particle morphology, they are generally powders of different particle sizes. Before obtaining the metallurgical copper-containing solid waste, it may undergo crushing, grinding, screening and other processing techniques. Therefore, the source of the sample and the general processing process can be inferred through the particle contour morphology, sample elements and phase composition of the metallurgical copper-containing solid waste. However, for the detection of whether it is metallurgical copper-containing solid waste, during the detection process, the sample to be analyzed should ensure that the particle contour morphology is clear and the surface is flat so as to accurately determine the composition. For example, samples prepared by conventional electron microscopy methods for powders, such as direct dispersion method, conductive adhesive bonding method, ultrasonic dispersion method, spray method, etc., cannot simultaneously meet the requirements of ensuring clear particle contour morphology and accurate composition determination and quantification. After repeated tests, the inventors found that the present invention adopts the powder cross-section observation method for scanning electron microscope analysis, that is, firstly, copper-containing powder, conductive epoxy resin and curing agent are cured to prepare two block samples to achieve the first embedding; then, the two block samples are embedded in a manner that the cross section of one block sample and the longitudinal section of the other block sample are placed in the same plane to achieve the second embedding, and then, after metallographic grinding and polishing, they are placed in the electron microscope for observation. The two-time embedding sample preparation method of the present invention can realize the observation of the powder cross section, and can overcome the problem that the sample on the cross section is not representative due to the different density of the powder particles, which causes the particles with high density to sink and the particles with low density to float during the static process, thereby improving the clarity of the sample particle contour morphology and the accuracy of the composition.
[0021] Preferably, in the particle size fingerprint information, the average particle size of the copper-containing solid waste is 18-45 μm.
[0022] Preferably, in the element fingerprint information, the copper-containing solid waste includes the following elemental components in mass percentage: S2-10%, Fe 8-15%, Cu 15-30%, Ti 0-1%, Zn 0-1%, O 15-40%, Si 10-25%, Ca 2-10%, Al 1.5-5%, K 0.5-5%, and Mg 0-5%.
[0023] Preferably, in the mineral fingerprint information, the copper-containing solid waste includes the following mineral phases in mass percentage: blue chalcocite 1-5%, Cu8S5 0-10%, chalcopyrite ≤15%, pyrite ≤10%, chalcopyrite ≤5%, and the remainder is other phases.
[0024] Preferably, based on the mass percentage of the copper-containing solid waste as 100%, the other phases include at least one of the following mineral phases in mass percentage: cuprite 0-10%, lithium tourmaline 0-3%, sodium pyroxene 0-35%, cancrystal 0-10%, potassium feldspar 0-7%, copper sulfate 0-6%, amphibole 0-5%, black hard chlorite 0-4%, and olivine 0-3%.
[0025] Preferably, in step (1), the drying temperature is 60-100° C., the drying time is 1-5 h, the drying is carried out under an inert gas, and the shaking time is 5-30 min.
[0026] Preferably, in step (2), the mass ratio of the copper-containing powder, the conductive epoxy resin and the curing agent is 1:(8-15):(1-2), the curing time is 12-48 hours, and the sizes of the two block samples are both 5 mm×5 mm×5 mm.
[0027] Preferably, in step (3), the embedded sample is a cylinder with a diameter of 25-35 mm, the embedding temperature is 120-160° C., and the embedding time is 3-10 min.
[0028] Preferably, in step (5), in the test, the acceleration voltage is 15-25 kV and the beam current parameter is 5-6.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) In the method of the present invention, the method of mounting the sample twice can fully consider the representativeness of the sample, avoid the result error caused by the uneven sample, and improve the comprehensiveness and accuracy of the detection and analysis; the conventional method needs to prepare the sample again when retesting the solid waste attribute identification sample, while the mounted sample prepared by the present method can be reused;
[0031] (2) The method of the present invention uses less consumables, equipment and personnel, and has low labor costs. The microscopic morphology, energy spectrum detection and mineral analysis of the sample are carried out simultaneously, which greatly improves work efficiency and accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the elemental composition analysis result diagram of sample 1-2.
[0033] Figure 2 This is the mineral phase analysis result diagram of sample 1-2.
[0034] Figure 3 This is the element distribution analysis result diagram of sample 1-2. Minerals with high copper content are rendered in red, and minerals and areas with low copper content are rendered in blue.
[0035] Figure 4 This is the element distribution analysis result diagram of sample 3. Minerals with high copper content are rendered in red, and minerals and areas with low copper content are rendered in blue. DETAILED DESCRIPTION
[0036] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can all be obtained from commercial channels. The following samples 1-3 are all samples sent for inspection at a customs port, the following conductive inlay materials are all conductive phenolic resins, and the following polishing liquid is a diamond suspension dedicated to metallography, and 1μ or 3μ represents the size of diamond particles in the suspension.
[0037] Example 1
[0038] (1) After the copper-containing material powder (sample 1) is fully mixed, 50 g of the powder is taken out by quartering, placed in a protective atmosphere furnace at 80° C. for 2 hours, taken out and cooled, and then placed in a sealed bag and shaken in an oscillator for 10 minutes to ensure that it is fully mixed and dispersed;
[0039] (2) Randomly take 2g of the 50g sample, add 20g of conductive epoxy resin and 2.4g of curing agent, place in a disposable small paper cup, and stir thoroughly with a glass rod to form a uniform suspension;
[0040] (3) Pour the suspension into two silica gel grids of 5 mm × 5 mm × 5 mm prepared in advance and let it stand for 24 hours;
[0041] (4) Place the two cured samples in a fully automatic mounting machine mold with a diameter of 30 mm so that the cross section and the longitudinal section are in the same plane, add about 10 g of conductive mounting material for electron microscopy, heat at 150°C for 8 minutes, and cool at a medium speed for 5 minutes to make a Φ30×20 (mm) cylindrical mounting sample;
[0042] (5) The mounted samples were ground for 5-10 minutes using a fully automatic metallographic grinding and polishing machine in the order of 200# special grinding disc, 600# sandpaper, 1200# sandpaper, and 9μ special polishing disc, and then polished for 5-10 minutes using a polishing cloth wheel and 3μ and 1μ special polishing liquids respectively; the polished samples were cleaned with clean water, dehydrated with anhydrous alcohol, blown dry, and placed in a drying bottle for 24 hours;
[0043] (6) Place the dried sample directly into an electron microscope for observation. If the sample has obvious discharge, perform vacuum carbon spraying on the observation surface.
[0044] (7) Observe and analyze using a scanning electron microscope (SEM) equipped with a dual energy dispersive spectrometer (EDS), with an accelerating voltage of 20 kV and a beam parameter of 5.50. Microscopic morphology is observed from low to high magnification, and backscattered images of typical particles are taken in backscattered electron mode;
[0045] According to the morphological characteristics of most particles of the samples collected by SEM, the elements contained in the collected particles are qualitatively analyzed by EDS to fully identify the element composition of the samples. At the same time, the elements contained in the samples are quantitatively and semi-quantitatively analyzed to give the element surface distribution.
[0046] The SEM images and EDS information of each particle are stitched together through software images, and the particle size information is measured and collected;
[0047] The above-mentioned SEM images and element surface distribution are input into the mineral analysis software, and the mineral standard library is used for comparison and matching analysis. The entire analysis is run by the automatic mineral analysis system, in which the composition data is collected by the software, and the element composition and mineral phase composition data are analyzed to finally obtain the mineral analysis data, determine the phase composition and specific mineral types, names, contents and distribution in the sample;
[0048] (8) Based on the above detection and analysis, the fingerprint characteristics of solid waste properties are summarized and refined, namely the microscopic morphological characteristics, mineral distribution, composition and content information under the scanning electron microscope, so as to accurately identify the properties of copper-containing solid waste.
[0049] Example 2-3
[0050] The difference between Example 2-3 and Example 1 is that the samples are different. The copper-containing material powders of Examples 2-3 are marked as Sample 2 and Sample 3, respectively, and the rest of the processes are the same.
[0051] The element composition, particle size, mineral phase type and content analysis results of samples 1-3 in Examples 1-3 are shown in Table 1-2 and Attached Figure 1-4 shown.
[0052] Table 1
[0053] element Sample 1 Sample 2 Sample 3 S 7.63 37.62 6.01 Fe 14.13 34.77 13.73 Cu 18.23 18.45 24.20 Ti - 3.64 - Zn - 2.44 - O 31.36 1.57 28.72 Si 15.57 0.98 14.08 Ca 5.84 - 6.95 Al 3.41 - 2.69 K 1.6 - 1.61 Mg - - 1.37
[0054] Table 2
[0055]
[0056] The inventors of the present invention have found that the fingerprint information of copper-containing smelting solid waste includes particle size fingerprint information, element fingerprint information and mineral fingerprint information, wherein the average particle size of copper-containing solid waste is ≥18μm; copper-containing solid waste includes the following elemental components by mass percentage: S≤11%, Fe≤17%, Cu 5-32%, Ti≤1.5%, Zn≤1.5%, O5-45%, Si≤30%, Ca≤10.5%, Al≤5.5%, K≤5.5%, Mg≤5.5%; copper-containing solid waste includes the following mineral phases by mass percentage: blue chalcocite 0.5-6%, Cu8S5 0.5-11%, chalcopyrite≤16%, pyrite≤10.5%, chalcopyrite≤5.5%, and the remainder is other phases. The properties of solid waste can be determined by the above-mentioned particle size fingerprint information, element fingerprint information and mineral fingerprint information.
[0057] Table 1-2 and Appendix Figure 1-4 It can be seen that the Cu content in samples 1-3 is similar, and the copper content in sample 3 is slightly higher; the Fe and S content in samples 1 and 3 is low, and the Fe and S content in sample 2 is high; the O, Si, Ca, Al and other element contents in samples 1 and 3 are higher than those in sample 1. It is impossible to distinguish whether samples 1-3 belong to copper-containing metallurgical solid waste based solely on the copper content. Based on the element fingerprint information of the above copper-containing smelting solid waste, it can be seen that samples 1 and 3 are consistent with the element fingerprint information of copper-containing smelting solid waste, and sample 2 is inconsistent with the element fingerprint information of copper-containing smelting solid waste.
[0058] Sample 1 contains a small amount of five copper-containing minerals, namely cuprite, Cu8S5, blue chalcocite and lithium tourmaline, as well as a large number of other substances without copper mineral phases. The phase characteristics of copper-containing minerals in Sample 1 are consistent with the mineral fingerprint information of copper-containing solid wastes; the element distribution diagram of Sample 1 shows that copper-containing minerals are mostly relatively coarse particles, with a D50 of 19.6-37.1μm, and the particle size characteristics of copper-containing particles in Sample 1 are consistent with the particle size fingerprint information of copper-containing solid wastes. It can be seen that the proportion of copper-containing mineral phases in Sample 1 is low, the particle size of copper-containing mineral phases is finer than other non-copper-containing particles, and the types of copper-containing minerals are complex. If the copper ore raw materials that have been beneficiated are generally processed through a complete beneficiation process, most of the minerals (about 80%) are uniform in particles, and most of the copper mineral monomers have been dissociated after passing through a 200-mesh sieve. The types of copper minerals are relatively simple and of high grade. Based on this, Sample 1 does not meet the characteristics of the copper ore beneficiation process and is determined to be a copper-containing solid waste.
[0059] Sample 2 mainly contains three kinds of copper-containing minerals, namely, chalcopyrite, pyrite and chalcopyrite. The copper-containing phases are all sulfides, and the proportion is relatively high. There are only a small amount of other non-copper minerals. The phase characteristics of the copper-containing minerals in Sample 2 are inconsistent with the mineral fingerprint information of copper-containing solid waste; the element distribution map shows that the copper-containing minerals are mostly particles with a D50 of 13.0-17.5μm. The particle size characteristics of the copper-containing particles in Sample 2 are inconsistent with the particle size fingerprint information of copper-containing solid waste. They are larger than other non-copper-containing particles, which is consistent with the characteristics of copper ore dressing process. It belongs to copper concentrate, not copper-containing solid waste.
[0060] Although the copper content in sample 3 is relatively high, it is mainly composed of gangue minerals such as pyroxene and nepheline. The physical characteristics of the copper-containing mineral phase in sample 3 are consistent with the mineral fingerprint information of copper-containing solid waste; the element distribution map shows that most of the copper-containing minerals are completely cleaved, which are clearly distinguished from low-copper content minerals, and their particle equivalent circle diameters are between 0.3-58.7μm. The sample was analyzed by particle size analysis, and the particle D50 was 25.1μm. Among them, the particle size of the copper-containing mineral phase is finer than that of other non-copper-containing particles. The particle size characteristics of the copper-containing particles in sample 3 are consistent with the particle size fingerprint information of copper-containing solid waste. From the sample element distribution results, it can be seen that this sample has not completed the mineral processing process and is determined to be a solid waste.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for identifying the properties of copper-containing solid waste, characterized in that: The steps include: (1) drying and shaking the copper-containing solid to be identified to obtain a copper-containing powder; (2) mixing the copper-containing powder, the conductive epoxy resin and the curing agent uniformly to obtain a mixture; transferring the mixture into two molds respectively, and curing to obtain two block samples; (3) placing the two block samples in a mounting device in such a manner that the cross section of one block sample and the longitudinal section of the other block sample are in the same plane, adding a conductive mounting material, and mounting to obtain a mounted sample; (4) polishing, cleaning and drying the mounted sample in sequence to obtain a sample to be tested; (5) using a scanning electron microscope to test the sample to be tested, collecting the particle morphology characteristics, element types and their contents, and element surface distribution information on the sample in a backscattered electron mode, and using the mineral standard library in the mineral analysis software for matching analysis to determine the mineral phases and their contents in the sample, and obtain the particle size information, element information, and mineral information of the sample; (6) comparing the particle size information, element information and mineral information of the sample with the fingerprint information of the copper-containing solid waste to determine whether the copper-containing solid to be identified is copper-containing solid waste; The fingerprint information of the copper-containing solid waste includes at least one of particle size fingerprint information, element fingerprint information and mineral fingerprint information; In the particle size fingerprint information, the average particle size of the copper-containing solid waste is ≥18 μm; In the element fingerprint information, the copper-containing solid waste includes the following element components in mass percentage: S≤11%, Fe≤17%, Cu 5-32%, Ti≤1.5%, Zn≤1.5%, O 5-45%, Si≤30%, Ca≤10.5%, Al≤5.5%, K≤5.5%, Mg≤5.5%; In the mineral fingerprint information, the copper-containing solid waste includes the following mineral phases in mass percentage: blue chalcocite 0.5-6%, Cu8S5 0.5-11%, chalcopyrite ≤16%, pyrite ≤10.5%, chalcopyrite ≤5.5%, and the remainder is other phases.
2. The method for identifying the properties of copper-containing solid waste according to claim 1, characterized in that: In the particle size fingerprint information, the average particle size of the copper-containing solid waste is 18-45 μm.
3. The method for identifying the properties of copper-containing solid waste according to claim 1, characterized in that: In the element fingerprint information, the copper-containing solid waste includes the following element components in mass percentage: S2-10%, Fe 8-15%, Cu 15-30%, Ti0-1%, Zn 0-1%, O 15-40%, Si 10-25%, Ca 2-10%, Al 1.5-5%, K 0.5-5%, and Mg 0-5%.
4. The method for identifying the properties of copper-containing solid waste according to claim 1, characterized in that: In the mineral fingerprint information, the copper-containing solid waste includes the following mineral phases in mass percentage: blue chalcocite 1-5%, Cu8S5 0-10%, chalcopyrite ≤15%, pyrite ≤10%, chalcopyrite ≤5%, and the remainder is other phases.
5. The method for identifying the properties of copper-containing solid waste according to claim 4, characterized in that: Taking the mass percentage of the copper-containing solid waste as 100%, the other phases include at least one of the following mineral phases in mass percentage: cuprite 0-10%, lithium tourmaline 0-3%, sodium pyroxene 0-35%, cancrystal 0-10%, potassium feldspar 0-7%, copper sulfate 0-6%, amphibole 0-5%, black hard chlorite 0-4%, and olivine 0-3%.
6. The method for identifying the properties of copper-containing solid waste according to claim 1, characterized in that: In step (1), the drying temperature is 60-100° C., the drying time is 1-5 h, the drying is carried out under an inert gas, and the shaking time is 5-30 min.
7. The method for identifying the properties of copper-containing solid waste according to claim 1, characterized in that: In step (2), the mass ratio of the copper-containing powder, the conductive epoxy resin and the curing agent is 1:(8-15):(1-2), the curing time is 12-48 hours, and the sizes of the two block samples are both 5mm×5mm×5mm.
8. The method for identifying the properties of copper-containing solid waste according to claim 1, characterized in that: In step (3), the embedded sample is a cylinder with a diameter of 25-35 mm, the embedding temperature is 120-160° C., and the embedding time is 3-10 min.
9. The method for identifying the properties of copper-containing solid waste according to claim 1, characterized in that: In step (5), in the test, the acceleration voltage is 15-25 kV and the beam current parameter is 5-6.